2018
DOI: 10.1016/j.devcel.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

A Futile Battle? Protein Quality Control and the Stress of Aging

Abstract: There exists a phenomenon in aging research whereby early life stress can have positive impacts on longevity. The mechanisms underlying these observations suggest a robust, long-lasting induction of cellular defense mechanisms. These include the various unfolded protein responses of the endoplasmic reticulum (ER), cytosol, and mitochondria. Indeed, ectopic induction of these pathways, in the absence of stress, is sufficient to increase lifespan in organisms as diverse as yeast, worms, and flies. Here, we provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 317 publications
(352 reference statements)
3
114
1
Order By: Relevance
“…CEBPb, ATF4, and CHOP are also key activators of the mitochondrial unfolded protein response (mtUPR) (Higuchi-Sanabria et al, 2018;Moehle et al, 2018); however, we did not observe significant upregulation of mitochondrial proteases in the Mrps12 ep/ep mice, perhaps due to a simultaneous induction of systems that stabilize mitochondrial respiratory complexes, as we observed in these mice at 10 weeks of age. We and others have previously observed increased ATF4 and CHOP in mouse models with impaired mitochondrial translation (Rackham et al, 2016;Seiferling et al, 2016;Perks et al, 2018), and impaired mitochondrial translation can induce mtUPR in worms and mammalian cell culture (Houtkooper et al, 2013).…”
Section: Of 19contrasting
confidence: 73%
“…CEBPb, ATF4, and CHOP are also key activators of the mitochondrial unfolded protein response (mtUPR) (Higuchi-Sanabria et al, 2018;Moehle et al, 2018); however, we did not observe significant upregulation of mitochondrial proteases in the Mrps12 ep/ep mice, perhaps due to a simultaneous induction of systems that stabilize mitochondrial respiratory complexes, as we observed in these mice at 10 weeks of age. We and others have previously observed increased ATF4 and CHOP in mouse models with impaired mitochondrial translation (Rackham et al, 2016;Seiferling et al, 2016;Perks et al, 2018), and impaired mitochondrial translation can induce mtUPR in worms and mammalian cell culture (Houtkooper et al, 2013).…”
Section: Of 19contrasting
confidence: 73%
“…Thus, the role of AMPK (i.e., AAK‐1 and AAK‐2) signaling in DR‐induced longevity may be broader than previously thought. As aging is often linked to accumulations of damaged proteins, maintaining protein homeostasis (or proteostasis) is critical for longevity regulation (Higuchi‐Sanabria, Frankino, Paul, Tronnes, & Dillin, 2018). Here, our findings suggest that DR may activate the AMPK‐eE2K axis to regulate proteostasis and consequently the rate of aging via inhibiting translation and elevating SG formation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial electron transport chain (ETC) perturbation via the downregulation of a complex IV subunit (cco-1) has been extensively described to dramatically increase longevity (Higuchi-Sanabria et al, 2018a;Moehle et al, 2018). Similar to neuronal xbp-1s animals, lipids are significantly decreased in cco-1 RNAi animals (Extended Data Fig.…”
Section: A Lipophagy Complex Mediates Cerm Formation and Lipid Turnovmentioning
confidence: 99%
“…lifespan, stress resistance). Work with C. elegans has shown that its cells become less capable in protein folding and also less able to induce stress responses to proteotoxicity with advanced age (Ben-Zvi et al, 2009;Brown and Naidoo, 2012;Dillin et al, 2002aDillin et al, , 2002bDurieux et al, 2011;Higuchi-Sanabria et al, 2018a;Taylor and Dillin, 2013). Interestingly, overexpression (OE) of the spliced version of xbp-1 (xbp-1-s) specifically in neurons, extends organismal lifespan and increases ER stress tolerance in a cell non-autonomous manner (Taylor and Dillin, 2013).…”
mentioning
confidence: 99%